A broadband ferromagnetic resonance dipper probe for magnetic damping measurements from 4.2 K to 300 K - He, Shikun (2016)
A dipper probe for broadband Ferromagnetic Resonance (FMR) operating from 4.2 K to room temperature is described. The apparatus is based on a 2-port transmitted microwave signal measurement with a grounded coplanar waveguide. The waveguide generates a microwave field and records the sample response. A 3-stage dipper design is adopted for fast and stable temperature control. The temperature variation due to FMR is in the milli-Kelvin range at liquid helium temperature. We also designed a novel FMR probe head with a spring-loaded sample holder. Improved signal-to-noise ratio and stability compared to a common FMR head are achieved. Using a superconducting vector magnet we demonstrate Gilbert damping measurements on two thin film samples using a vector network analyzer with frequency up to 26 GHz: (1) A Permalloy film of 5 nm thickness and (2) a CoFeB film of 1.5 nm thickness. Experiments were performed with the applied magnetic field parallel and perpendicular to the film plane.